The Effect of Audio Visual Media on the Knowledge and Attitudes of Mothers of Babies 0-24 Months About Giving Measles Booster Immunization in the Work Area of the Hutapaung Health Center in 2022 - Lia Rosa Veronika Sinaga; Henny Arwina Bangun; Jasmen Manurung; Yuris R. A. Marbun (TOUR HEALTH JOURNAL, 2022)
Background: Several types of basic immunizations are given when babies require a booster dose to increase their immunity, one of which is through the provision of follow-up immunizations at the age of 18 months. Nationally, one of the booster immunization programs is the measles booster immunization. Purpose: This study aims to determine the effect of audio-visual media on the knowledge and attitudes of mothers of infants 0-24 months about giving measles booster immunization in the Hutapaung Health Center Work Area. Method: This research is a quantitative research in the form of pre-experimental design with a one-group pretest-posttest research design. The population of this study were all mothers who had babies 0-24 months (baduta) and 180 people had not done measles booster immunization to their children. The sampling technique in this study was using a random sampling technique using the Slovin formula as many as 64 people, then to determine the number of mothers under the age of five who were sampled in each village, the proportional stratified random sampling technique was used. The research instrument used a questionnaire sheet. Results:  The results obtained p-value = 0.000 for both the knowledge variable and the attitude variable. Discussion and Conclusion: The conclusion is that there is an effect of audio-visual media on the knowledge and attitudes of mothers of infants 0-24 months about giving measles booster immunization. So it is necessary to develop health counseling activities both outside the building and inside the building using audio-visual media in order to improve the knowledge and attitudes of mothers for the better.